2005
DOI: 10.1007/s11064-005-8799-7
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine Protects the Brain of Rats and Mongolian Gerbils against Ischemic Injury: After-Stroke-Effect

Abstract: Carnosine, a specific constituent of excitable tissues of vertebrates, exhibits a significant antioxidant protecting effect on the brain damaged by ischemic-reperfusion injury when it was administered to the animals before ischemic episode. In this study, the therapeutic effect of carnosine was estimated on animals when this drug was administered intraperitoneally (100 mg/kg body weight) after ischemic episode induced by experimental global brain ischemia. Treatment of the animals with carnosine after ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 27 publications
1
56
0
2
Order By: Relevance
“…Our results are consistent with previous studies showing that exogenously administered carnosine evoked a marked reduction in infarct size when administered before the ischemic injury either in adult and neonatal rat models [49][50][51]. Carnosine has been reported to exert protective effects on neurological symptoms and animal mortality even when injected into the blood stream after the ischemic event [52]. Here for the first time we show that a marked reduction in the mean size of the ischemic area was also measured when two carnosinase-stable derivatives, compound 7e and its des-NO analogue 7a, were administered at 500 mg/kg, without any significant difference among groups.…”
Section: Cerebral Ischemia-reperfusion Injurysupporting
confidence: 93%
“…Our results are consistent with previous studies showing that exogenously administered carnosine evoked a marked reduction in infarct size when administered before the ischemic injury either in adult and neonatal rat models [49][50][51]. Carnosine has been reported to exert protective effects on neurological symptoms and animal mortality even when injected into the blood stream after the ischemic event [52]. Here for the first time we show that a marked reduction in the mean size of the ischemic area was also measured when two carnosinase-stable derivatives, compound 7e and its des-NO analogue 7a, were administered at 500 mg/kg, without any significant difference among groups.…”
Section: Cerebral Ischemia-reperfusion Injurysupporting
confidence: 93%
“…3). Recently, carnosine has been shown to protect cultured neurons from oxygen glucose deprivation and to exhibit neuroprotective properties in animal models of global and cerebral ischemia (17,38,39). Therefore, our data suggest that carnosine and anserine may be attractive candidate for treatment of neurodegenerative disorders.…”
Section: Resultsmentioning
confidence: 65%
“…Carnosine also acts as a copper chelator and is known to induce rejuvenating effects, to participate in neuroprotective actions that preserve cell survival, to suppress cell senescence, and to possess anti-cross linking properties (15,16). Several studies suggest that exogenously administrated carnosine has a neuroprotective effects against brain injury resulting from a variety of different causes (17)(18)(19). Additionally, carnosine possesses a low toxicity, as demonstrated in mammalian systems, and it is found exclusively in animal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that CAR could inhibit lipid peroxidation and protein oxidation (9 -11). Therefore, CAR may be an effective agent to decrease prooxidant status in oxidative stress-induced pathologies such as ischemia-reperfusion (12,13), liver damage (14,15), and aging (16 -19). In the literature, there is no study investigating the in vivo effect of CAR in chronic stress-exposed rats.…”
Section: Introductionmentioning
confidence: 99%